Prevalence of Influenza Viruses (Influenza Like Illness) In Regional Laboratory Avian Influenza Semarang - Wahyutomo, Ridha; Ciptaningtyas, V. Rizke; Hadi, Purnomo (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: Influenza is the major health threat worldwide causing illness and death every year. However, data on the epidemiology of influenza in tropical countries, including Indonesia, are still limited. Up dated data for its prevalence is needed to monitor its spreading and to evaluate its outbreak. Therefore a working regional laboratory in surveillance of ILI (Influenza Like Illness) was formed. This research was conducted to provide updated data on prevalence of ILI in regional laboratorium avian influenza Semarang.Design and Method: Data from patients examined in the regional laboratory of avian influenza Semarang from April 2009 until December 2010 was collected. Samples were obtained from Malang sentinel, Yogyakarta sentinel and Semarang sentinel. Samples were examined using PCR to detect influenza A, influenza B, and swine flu.Result: out 1367 patients tested, 279 patients (20.41%) were from Yogyakarta sentinel, 619 patients (45.28%) were from Malang sentinel, and 467 patients (34.16%) were from Semarang sentinel. Flu A virus was detected in 117 patients (8.5%). Influenza B virus was found in 39 patients (2.8%). H1 virus was detected in 5 patients (0.36%). H3 virus was detected in 45 patients (3.29%). Swine flu virus was detected in 3 patients in Malang.Conclusion: The highest prevalence of flu A and flu B examined in avian influenza regional laboratory Semarang was from Semarang sentinel, followed by Yogyakarta sentinel and Malang (Sains Medika, 3(2):157-161).